Efektivitas Reward dan Punishment Terhadap Kedispilinan Anak Usia Dini di RA Miftahul Ulum Jayasari - Ai Siska Silvia Zahara; Dela Zahara; Tiara Dewi Lestari; Esa Eryani; Fitria Himatul Aliyah; Nuri Andiani Putri (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
Reward and punishment is an educational tool for educators' efforts to improve behavior and character as a consequence according to student actions. The purpose of this study was to determine the effectiveness of reward and punishment for early childhood discipline. This research examines in depth the effectiveness of reward and punishment on early childhood discipline at RA Miftahul Ulum Jayasari. The results of the research show that reward and punishment are very effective in increasing discipline. The benefits of giving reward and punishment at RA Miftahul Ulum Jayasari make children more aware of their actions. Like a child who often comes late to be punctual, a lack of focus in learning becomes more focused, and a quiet child becomes active in everything.